Patients With Myeloproliferative Neoplasms Harbor High Frequencies of CD8 T Cell-Platelet Aggregates Associated With T Cell Suppression - Carnaz Simões, Ana Micaela; Holmström, Morten Orebo; Aehnlich, Pia; Rahbech, Anne; Peeters, Marlies J. W.; Radziwon-Balicka, Aneta; Zamora, Carlos; Wirenfeldt Klausen, Tobias; Skov, Vibe; Kjær, Lasse; Ellervik, Christina; Fassi, Daniel El; et al. (Frontiers in Immunology, 2022)
Myeloproliferative neoplasms (MPN) are chronic cancers of the hematopoietic stem cells in the bone marrow, and patients often harbor elevated numbers of circulating platelets (PLT). We investigated the frequencies of circulating PLT-lymphocyte aggregates in MPN patients and the effect of PLT-binding on CD8 T cell function. The phenotype of these aggregates was evaluated in 50 MPN patients and 24 controls, using flow cytometry. In vitro studies compared the proliferation, cytokine release, and cytoxicity of PLT-bound and PLT-free CD8 T cells. Frequencies of PLT-CD8 T cell aggregates, were significantly elevated in MPN patients. Advanced-disease stage and CALR mutation associated with the highest aggregate frequencies with a predominance of PLT-binding to antigen-experienced CD8 T cells. PLT-bound CD8 T cells showed reduction in proliferation and cytotoxic capacity. Our data suggest that CD8 T cell responses are jeopardized in MPN patients. JAK2 and CALR exon 9 mutations – the two predominant driver mutations in MPN – are targets for natural T cell responses in MPN patients. Moreover, MPN patients have more infections compared to background. Thus, PLT binding to antigen experienced CD8 T cells could play a role in the inadequacy of the immune system to control MPN disease progression and prevent recurrent infections.